Considering dark tourism as an opportunity to reflect on unsettling historical events. English for Tourism university students research on ethical dark tourism sites and tours - Alessandra Ficarra (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2022)
English for Tourism (EfT) university courses offer students the opportunities to enhance their English language learning specific skills to be used in the tourism industry. Communicative approach and authentic material contextualized to the professional field are the leading practices in EfT courses. However, not only is EfT a multi-subject field covering geography, history and economics: it may also be considered as a powerful means of meeting, exchange and education at international level. This article is a report of a teaching experience, where EfT course students have been invited to research on international dark tourism sites and to elaborate presentations to be given in class. The dark tourism debated in the class represented for the students a precious educational opportunity to hear about unsung heroes, develop meaningful connections with contemporary socio-economic dynamics and experience tourism, exceptionally, as an ethical act of unearthing pieces of unwritten history.DOI: 10.26905/enjourme.v7i1.7506